1997
DOI: 10.1103/physrevlett.78.3471
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Ion-Temperature-Gradient–Driven Tokamak Modes by Magnetic-Field Gradient Reversal

Abstract: Global gyrokinetic particle simulations have been used to search tokamak configurations which are stable against the ion-temperature-gradient-driven (ITG) modes commonly held responsible for the core anomalous ion heat transport. The stable configurations are characterized by strongly reduced or reversed =B drifts on the low-field side. Since excellent transport properties have been observed in high b p (poloidal beta) tokamak experiments, we conjecture, as a result of our simulations, that this may be due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Electrostatic approximation clearly breaks down when ␣ e approaches the critical value found in this study and in this respect the analysis in Ref. 7 is not self-consistent.…”
Section: ͑16͒mentioning
confidence: 61%
See 1 more Smart Citation
“…Electrostatic approximation clearly breaks down when ␣ e approaches the critical value found in this study and in this respect the analysis in Ref. 7 is not self-consistent.…”
Section: ͑16͒mentioning
confidence: 61%
“…Recently, Fivaz et al 7 analyzed the ITG mode in electrostatic approximation with the effects of drift reversal in the magnetic drift frequency,…”
Section: ͑16͒mentioning
confidence: 99%
“…Our numerical results corroborate their findings, and show that neglect of δB for A = 3 and A = 1.4 for these cases leads to an underestimate of the growth rate by factors of two to an order of magnitude or more. Analyses of advanced tokamak cases at both A = 1.4 and A = 3 have frequently neglected this effect [19], probably leading to a substantial underestimate of instability strength.…”
Section: Resultsmentioning
confidence: 99%
“…Stabilization of microinstabilities via this mechanism has been proposed previously. 4 However, Berk and Dominguez 1 showed that this stabilizing effect is canceled by including compressional magnetic field fluctuations, which allow the plasma to carry its "self-dug" well. For this reason, the importance of retaining B ʈ in stability calculations at high ␤ has been commented on by other authors.…”
Section: ͑2͒mentioning
confidence: 97%